(untitled) (Research Nepal Journal of Development Studies, 2024)
The Shreemadbhagavadgeeta, a seminal-influential philosophical scripture of the Sanatan Vedic tradition, presents a timeless dialogue on human ethics, duty, and liberation that resonates deeply with the contemporary global vision of sustainable development. This research undertakes a hermeneutic analysis of the Geeta to explore its interpretative relevance to the People Pillar of sustainable development—one of the three fundamental pillars recognized by the United Nations, alongside Planet and Prosperity. Using Gadamer’s philosophical hermeneutics as an interpretative framework, this study interprets select verses of the Gita through the lens of Sustainable Development Goals (SDGs 1–5), emphasizing poverty eradication, health, education, gender equality, and social justice. The findings reveal that the Gita envisions human development not as material accumulation but as a harmonization of inner virtue (dharma) and outer responsibility (karma yoga). It advocates for equality, selfless service, and compassion as the moral foundations of a sustainable society. Through the hermeneutic circle of understanding, the research discovers that the Gita’s metaphysical insights align with the spiritual dimension of sustainability, wherein human well-being is inseparable from moral consciousness and social equity. This study contributes to global sustainability discourse by bridging Eastern spiritual philosophy with Western development theory, affirming that sustainable development must be grounded in ethical transformation and self-realization to achieve peace, justice, and human dignity.